IMPROVING POPULATION MANAGEMENT AND HARVEST QUOTAS OF MOOSE IN RUSSIA - Glushkov, Vladimir M (Lakehead University, 2009)
Annual harvest quotas for moose and other game species in Russia have been based on population estimates derived from traditional winter track counts and hunter surveys. This labor-intensive approach has failed to account for evident changes in population density of moose. Specifically, regional differences in survival and mortality data and the impact of increased poaching are not measured or included in population estimates, and overharvest of moose occurs. I propose implementing a standard management approach similar to that used in other countries with moose populations that includes population trend analyses, productivity and mortality data, and a regional management approach. Such changes will improve the professional management of moose and other game species in Russia.